دور علم النحو في تعليم مهارة الكلام (تحليل في طلاب قسم تعليم اللغة العربية، الجامعة الإسلامية الحكومية ترناتي) - Sugirma, Sugirma; Hamid, M. Abdul; Agustang K, Agustang K; Hamzah, Hamzah (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
The science of Nahwu plays a crucial role in establishing a solid foundation for the development of speaking skills. This research aims to explore and analyze the role of Nahwu in learning the skill of speaking for students, utilizing a qualitative approach. The research method employed is a case study with participants from third-year students in the Arabic Language Education Department. Data was collected through in-depth interviews and analysis of documents related to the curriculum in the Arabic Language Education Department at the State Islamic Institute of Ternate. The research results indicate that understanding Nahwu has a significant impact on improving students' speaking skills. The application of Nahwu in learning contributes to enhancing fluency, accurate word selection, and a better understanding of sentence structure. Additionally, the study provides recommendations for the development of more effective curricula that integrate Nahwu in learning speaking skills. The anticipated effects of this research are expected to contribute to a deeper understanding of the importance of Nahwu in the context of learning the Arabic language, providing practical guidance for curriculum development at the college level.